Anle138b Partly Ameliorates Motor Deficits Despite Failure of Neuroprotection in a Model of Advanced Multiple System Atrophy - Fellner, Lisa; Kuzdas-Wood, Daniela; Levin, Johannes; Ryazanov, Sergey; Leonov, Andrei; Griesinger, Christian; Giese, Armin; Wenning, Gregor K.; Stefanova, Nadia (Frontiers in Neuroscience, 2016)
The neurodegenerative disorder multiple system atrophy (MSA) is characterized by autonomic failure, cerebellar ataxia and parkinsonism in any combination associated with predominantly oligodendroglial α-synuclein (α-syn) aggregates (glial cytoplasmic inclusions=GCIs). To date, there is no effective disease modifying therapy. Previous experiments have shown that the aggregation inhibitor anle138b reduces neurodegeneration, as well as behavioral deficits in both transgenic and toxin mouse models of Parkinson’s disease (PD). Here we analyzed whether anle138b improves motor skills and reduces neuronal loss, as well as oligodendroglial α-syn aggregation in the PLP-α-syn transgenic mouse challenged with the mitochondrial toxin 3-nitropropionic acid (3-NP) to model full-blown MSA. Following one month of treatment with anle138b, MSA mice showed signs of motor improvement affecting stride length, but not pole, grip strength and beam test performance. Loss of dopaminergic nigral neurons and Purkinje cells was not attenuated and GCI density remained unchanged. These data suggest that the pathology in transgenic PLP-α-syn mice receiving 3-NP might be too advanced to detect significant effects of anle138b treatment on neuronal loss and intracytoplasmic α-syn inclusion bodies. However, the partial motor amelioration may indicate potential efficacy of anle138b treatment that may be mediated by its actions on α-syn oligomers or may reflect improvement of neuronal dysfunction in neural at risk populations. Further studies are required to address the efficacy of anle138b in transgenic α-syn models of early-stage MSA and in the absence of additional toxin application.